The Influence of Service Quality, Tuition Fee and Promotion on Student Decisions to Continue Study in Postgraduate of Prima Indonesia University - Regina Fortunata; Nagian Toni (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The Prima Indonesia University (UNPRI) Postgraduate School is one of the Postgraduate programs in Medan. Various efforts to maintain and improve service quality have been made, as well as tuition fees have been set within an affordable and competitive range, as well as intense promotion, however these efforts have not succeeded in increasing the number of UNPRI Postgraduate School students, instead they have decreased each year. The purpose of this study is to find the factors that cause the low number of student registrants and develop alternative strategies and policies that can be implemented by management. UNPRI School to increase the number of student registrants through quality service, tuition fees, and promotions. This type of research is survey research. The questionnaire was distributed by clustered random sampling to 89 active students at the UNPRI Postgraduate School. From the results of the analysis, it was found that 42.7% of the decisions of students registering to continue their studies at the UNPRI Postgraduate School were influenced by Service Quality, Tuition, and Promotion, while 57.3% were influenced by other variables outside the variables used in this study. Service quality variables, tuition fees, and promotions together significantly influence student decisions. However, based on partial testing, the variable tuition does not significantly affect student decisions. On the contrary, service quality and promotion variables have a significant effect partially on student decisions.